Ta?w?r was?lah ta‘l?m al-lughah al-‘Arabiyyah al-taf?‘uliyyah ‘al? as?s al-lu‘bah al-ta‘l?miyyah Quizizz f? m?ddat al-mubtada’ wa-al-khabar li-?ull?b al-?aff al-‘?shir bi-al-madrasah al-‘?liyyah al-?uk?miyyah F?l?f? - Tosimpak, Hasanuddin; Takwim, Mardi; Hayah, Izza Vithry (Institut Agama Islam Negeri (IAIN) Palopo, 2023)
AbstractThis research aims to identify the development process and the level of validity of the developed product. The type of research is Research and Development (R&D) using the D4 development model, which consists of four stages: definition, design, development, and dissemination. The research subjects are tenth-grade students at Valuvu State Senior High School. Data collection methods used are observation, interviews, validation sheets, student response questionnaires, and documents. The data were analyzed using qualitative and quantitative data analysis methods. The result of this research and development is interactive Arabic language teaching media based on the Quizizz educational game in the subject of Mubtada and Khabar for tenth-grade students at Valuvu State Senior High School. Product validation results are as follows: 1) validation by subject matter experts scored 90.91%; 2) media experts scored 96.92%; 3) language experts scored 82.86%; 4) educational experts scored 97.65%. Based on these results, it can be concluded that the developed teaching media is highly valid for application in Arabic language teaching.Keywords: interactive teaching media, Quizizz educational game, Mubtada and Khabar.???????? ??? ????? ??? ????? ????? ??????? ?????? ?????? ?????? ??????. ??? ????? ?? ????? ???????? (R&D) ???????? ????? ????? D4 ???? ????? ?? ???? ????? ??? ????? ???????? ????????? ????????? ?????????. ????? ????? ?? ???? ???? ?????? ???????? ??????? ???????? ??????. ??????? ??? ???????? ????????? ?? ???????? ????????? ?????? ?????? ?? ????? ????????? ??????? ?????? ????????. ??? ????? ???????? ???????? ?????? ????? ???????? ??????? ???????. ????? ??? ????? ???????? ?? ????? ????? ????? ??????? ????????? ??? ???? ?????? ????????? ?????? ?? ???? ??????? ?????? ????? ???? ?????? ???????? ??????? ???????? ??????. ????? ?????? ?? ??? ??????:1) ?????? ?? ????? ?? ??? ???? ?????? ??? ??? ???? 90.91%? 2) ????? ??????? ??? ??? 96.92%? 3) ????? ????? ??? ??? 82.86%? 4) ????? ??????? ??? ??? 97.65%. ????? ??? ???????? ???? ??????? ?? ????? ??????? ??????? ????? ???? ??????? ?? ????? ????? ???????.??????? ????????: ????? ??????? ?????????? ?????? ????????? ??????? ??????? ??????